Enjeux et fractures de la Bolivie en 2009 - Sébastien Hardy (EchoGéo)
The third legally organized referendum under the mandate of President Evo Morales (2006-2010) took place on January 25, 2009. What is at stake in this consultation is the approval of the text of a new Constitution for Bolivia, and the limitation of the area of the land ownership. The results taken as a whole lead one to believe that the proposals of the President satisfy Bolivians. However, by looking at the bigger picture, one finds the traditional dissensions which have polarized the country for a long time, and continue to do so.